Environmental Variables for Sustainable Industry Performance with the Green Marketing Mix: Preliminary Study - Bambang Hengky Rainanto, Abdul Talib Bon, Jan Horas V. Purba (International Journal of Advanced Science and Technology, 2020)
This preliminary study is to determine the relationship between the variable Environmental Management System (EMS) and Pro-Environmental Behavior in hotel industry players for Sustainable Industry Performance (SIP) with the 7Ps Green Marketing Mix (GMM) as mediator. The pilot study was conducted at hotels in the city of Bogor, Indonesia. The background of the research is based on the increasingly frequent occurrence of environmental impacts due to the impact of tourism development. Hotel is one of the main industries that support tourism needs to create internal and environmental conditions in order to be able to do business sustainably. This initial research is expected to be a reference conceptual scientific model for research with a broader area or other fields related to the environment and the tourism sector. The results of this initial research will be important for other research in the hotel industry and the world of tourism with the aim of ensuring the sustainability of their business. The same research variable, but different types of objects and research locations, will likely give different results as well.